Neighborhood environmental exposures and incidence of attention deficit/hyperactivity disorder: A population-based cohort study. (March 2022) - Yuchi, Weiran; Brauer, Michael; Czekajlo, Agatha; Davies, Hugh W.; Davis, Zoë; Guhn, Martin; Jarvis, Ingrid; Jerrett, Michael; Nesbitt, Lorien; Oberlander, Tim F.; Sbihi, Hind; Su, Jason; et al.
Highlights: Greenness was associated with a lower incidence of childhood ADHD. PM2.5, but not NO2 or noise, was associated with an increased incidence of ADHD. There was a disproportionate risk of ADHD in high PM2.5 and low greenness areas. Vegetation percentage is a novel and precise greenness estimate. Abstract: Background: Emerging studies have associated low greenspace and high air pollution exposure with risk of child attention deficit/hyperactivity disorder (ADHD). Population-based studies are limited, however, and joint effects are rarely evaluated. We investigated associations of ADHD incidence with greenspace, air pollution, and noise in a population-based birth cohort. Methods: We assembled a cohort from administrative data of births from 2000 to 2001 (N ∼ 37, 000) in Metro Vancouver, Canada. ADHD was identified by hospital records, physician visits, and prescriptions. Cox proportional hazards models were applied to assess associations between environmental exposures and ADHD incidence adjusting for available covariates. Greenspace was estimated using vegetation percentage derived from linear spectral unmixing of Landsat imagery. Fine particulate matter (PM2.5 ) and nitrogen dioxide (NO2 ) were estimated using land use regression models; noise was estimated using a deterministic model. Exposure period was from birth until the age of three. Joint effects of greenspace and PM2.5 were analysed in two-exposure models and by categorizing values into quintiles. Results: During seven-year follow-up, 1217 ADHD cases were diagnosed. Greenspace was associated with lower incidence of ADHD (hazard ratio, HR: 0.90 [0.81–0.99] per interquartile range increment), while PM2.5 was associated with increased incidence (HR: 1.11 [1.06–1.17] per interquartile range increment). NO2 (HR: 1.01 [0.96, 1.07]) and noise (HR: 1.00 [0.95, 1.05]) were not associated with ADHD. There was a 50% decrease in the HR for ADHD in locations with the lowest PM2.5 and highest greenspace exposure, compared to a 62% increase in HR in locations with the highest PM2.5 and lowest greenspace exposure. Effects of PM2.5 were attenuated by greenspace in two-exposure models. Conclusions: We found evidence suggesting environmental inequalities where children living in greener neighborhoods with low air pollution had substantially lower risk of ADHD compared to those with higher air pollution and lower greenspace exposure.